HEALTH ETHICS EDUCATION: KNOWLEDGE, ATTITUDES AND PRACTICE OF HEALTHCARE ETHICS AMONG INTERNS AND RESIDENTS IN PAKISTAN - Imran, Nazish; Haider, Imran Ijaz; Jawaid, Masood; Mazhar, Nauman (Journal of Postgraduate Medical Institute, 2015)
Objective: To assess the knowledge, attitudes, and practices among internsand residents about healthcare ethics in an attempt to assist in developmentof ethics curriculum in Pakistan. Methodology: Four hundred respondents comprising of interns, junior and seniorpostgraduate trainees were recruited from two Public sector teachinginstitutions in different provinces of Pakistan for this cross sectional study. Aself- administered questionnaire was used to collect data. Data was analysedusing SPSS-17. Results: More than half of the respondents in all three groups encounteredethical problems on daily basis. These ethical issues were being discussed withthe clinical supervisor in only 25% of the instances. Unethical behaviour of seniorstowards junior doctors and patients were observed by more than threequarter of the respondents. A very high proportion of respondents (57%) hadno knowledge of code of ethics of Pakistan Medical and Dental council. Helsinkideclaration was known only to a few individuals. There were differencebetween interns, junior and senior residents with respect to their views aboutadherence to patient's wishes, paternalistic attitude of physicians, treatmentof children without parental consent, euthanasia, confidentiality and treatmentof noncompliant patients. Conclusion: Junior doctors representing different levels of training in Pakistanface ethical dilemmas on a regular basis but their current teaching and trainingin ethics is insufficient to help them deal with these competently.